Inhibition of the anti-apoptotic protein BCL2 in EML4-ALK cell models as a second proposed therapeutic target for non-small cell lung cancer. - Richard Junior Zapata Dongo; Diletta Fontana; Luca Mologni; Juan Enrique Faya Castillo; Stefany Fiorella Infante Varillas (PLoS ONE, 2025)
The anaplastic lymphoma kinase (ALK) oncoprotein plays a crucial role in non-small cell lung cancer (NSCLC) by activating signaling pathways involved in cell proliferation and survival through constitutive phosphorylation. While first-line crizotinib can regulate phosphorylation, mutations in the ALK gene can lead to resistance against ALK inhibitors (ALKi) such as ceritinib and alectinib. On the other hand, overexpression of BCL2, a protein involved in cell death regulation, has been observed in NSCLC and is considered a potential therapeutic target. In this study, we propose to inhibit BCL2 as a secondary therapeutic target in EML4-ALK cell models to overcome resistance caused by ALK mutations. Four Ba/F3 EML4-ALK cell models (WT, C1156Y, L1196M, and G1202R) generated by site-directed mutagenesis exhibited varying levels of BCL2 expression. Both the WT and G1202R models showed overexpression of BCL2, while C1156Y and L1196M models approached baseline levels. We treated these cells with ABT-199, a selective BCL2 inhibitor, and found that models with high BCL2 expression exhibited resistance, while those with lower expression showed sensitivity to BCL2 inhibition. In addition, our analysis using bioinformatics indicated that ABT-199 not only targets BCL2 but also binds to the active site of all ALK mutants, it was contrasted by in vitro ALK kinase activity inhibition by ABT-199 (5.5 μM). This interaction was further supported by a significant decrease of ALK phosphorylation in single and combination treatment with 300nM ABT-199. Finally, when ABT-199 was combined with ALKi, we observed a wide range of synergistic effects in the WT and G1202R cell models, while the C1156Y and L1196M models showed limited synergy. In conclusion, our findings indicate that BCL2 targeting with ABT-199, in combination with ALKi, can significantly reduce tumor cell survival in Ba/F3 EML4-ALK cell models.